Mechanisms of quorum sensing and strategies for quorum sensing disruption in aquaculture pathogens. Issue 9 (15th September 2014) - Zhao, J; Chen, M; Quan, CS; Fan, SD
Abstract In many countries, infectious diseases are a considerable threat to aquaculture. The pathogenicity of micro‐organisms that infect aquaculture systems is closely related to the release of virulence factors and the formation of biofilms, both of which are regulated by quorum sensing (QS). Thus, QS disruption is a potential strategy for preventing disease in aquaculture systems. QS inhibitors (QSIs) not only inhibit the expression of virulence‐associated genes but also attenuate the virulence of aquaculture pathogens. In this review, we discuss QS systems in important aquaculture pathogens and focus on the relationship between QS mechanisms and bacterial virulence in aquaculture. We further elucidate QS disruption strategies for targeting aquaculture pathogens. Four main types of QSIs that target aquaculture pathogens are discussed based on their mechanisms of action.